2022
DOI: 10.1155/2022/1698571
|View full text |Cite
|
Sign up to set email alerts
|

Exploration in the Mechanism of Zhisou San for the Treatment of Cough Variant Asthma Based on Network Pharmacology

Abstract: Background. Cough variant asthma (CVA) has no definitive diagnosis or pathogenic causes, and there is currently no effective and safe treatment. Methods. The network pharmacology was employed to investigate possible targets of Zhisou San (ZSS) in CVA treatment. The main chemical constituents of seven herbs in ZSS were collected based on the TCMSP. To explain the main mechanism, we sequentially screened the targets of each active ingredient and constructed the network of “herb-ingredient-target-disease.” The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The therapeutic mechanism of HM on chronic cough has been proposed in various ways. Among the included studies, Zhisou-san, or its modified form, was used most frequently, which was reported to be related to inflammation and Th17/Treg immune balance regulation for the treatment of CVA ( Guo et al, 2022 ). In addition, the pulmonary protective effect and antitussive effect of P. grandiflorus (Jacq.)…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic mechanism of HM on chronic cough has been proposed in various ways. Among the included studies, Zhisou-san, or its modified form, was used most frequently, which was reported to be related to inflammation and Th17/Treg immune balance regulation for the treatment of CVA ( Guo et al, 2022 ). In addition, the pulmonary protective effect and antitussive effect of P. grandiflorus (Jacq.)…”
Section: Discussionmentioning
confidence: 99%